2021
DOI: 10.1177/21582440211029927
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Instructors’ Cognitive Structure Toward the Academic Use of Social Network Sites: The Means–End Chain Theory

Abstract: Employing social network sites (SNSs) for academic purposes has been investigated in the literature; however, there is not enough scientific knowledge about university instructors’ behavioral perceptions and values that drive their academic use of SNSs. Therefore, a systematic cognitive framework, regarding SNSs academic usage, is beneficial to understand these behavioral perceptions. This research utilizes the means–end chain (MEC) analysis approach to investigate university instructors’ cognitive structure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Zhang and Yuan (2020) used the theory to determine which resource factors affect the perceived quality of information on academic social networking sites. Al‐Abdullatif and Aladsani (2021) discovered that academic social networking sites have seven key attributes that enable users to obtain 10 benefits and that are associated with nine values. In addition, Skalkos et al (2020) reported that whether Internet users use privacy‐enhancing software is not only influenced by the attributes and functions of the software but also influenced by whether using the software satisfies the users' personal needs, enables them to conform to social influences, and is in line with their personal values.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Zhang and Yuan (2020) used the theory to determine which resource factors affect the perceived quality of information on academic social networking sites. Al‐Abdullatif and Aladsani (2021) discovered that academic social networking sites have seven key attributes that enable users to obtain 10 benefits and that are associated with nine values. In addition, Skalkos et al (2020) reported that whether Internet users use privacy‐enhancing software is not only influenced by the attributes and functions of the software but also influenced by whether using the software satisfies the users' personal needs, enables them to conform to social influences, and is in line with their personal values.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For example, “size” as an attribute can lead to “convenient” as a consequence, which can then lead to “satisfaction” as a value (Al‐Abdullatif1 & Aladsani, 2021). In the context of the present study, the aim of MECA is to understand how individuals with mental illness perceive their use of Facebook private groups for the purpose of self‐disclosure.…”
Section: Introductionmentioning
confidence: 99%